Asteroseismic constraints on active latitudes of solar-type stars: HD 173701 has active bands at higher latitudes than the Sun. Issue 3 (20th March 2019) - Thomas, Alexandra E L; Chaplin, William J; Davies, Guy R; Howe, Rachel; Santos, Ângela R G; Elsworth, Yvonne; Miglio, Andrea; Campante, Tiago; Cunha, Margarida S
ABSTRACT: We present a new method for determining the location of active bands of latitude on solar-type stars, which uses stellar-cycle-induced frequency shifts of detectable solar-like oscillations. When near-surface activity is distributed in a non-homogeneous manner, oscillation modes of different angular degree and azimuthal order will have their frequencies shifted by different amounts. We use this simple concept, coupled to a model for the spatial distribution of the near-surface activity, to develop two methods that use the frequency shifts to infer minimum and maximum latitudes for the active bands. Our methods respond to the range in latitude over which there is significant magnetic flux present, over and above weak basal ephemeral flux levels. We verify that we are able to draw accurate inferences in the solar case, using Sun-as-a-star helioseismic data and artificial data. We then apply our methods to Kepler data on the solar analogue HD 173701, and find that its active bands straddle a much wider range in latitude than do the bands on the Sun.